Mobile and web technology to display notifications of academic events of the Universidad Francisco de Paula Santander by using the agile methodology for mobile development (2020)
The "Universidad Francisco de Paula Santander, Colombia" lacks a dynamic tool to give the academic community timely knowledge of events and information needs in an assertive manner and in a reasonable time. Based on the above and following the dissemination strategy designed by the "Centro de Comunicaciones y Medios Audiovisuales" to incorporate the use of technology to massify internal institutional information, is built the mobile application NotiUFPS for Android devices, which allows notifying all events that take place at the university, including the calendar of previous and academic calendar, with the compatibility of downloading information in pdf format. The application will make use of global positioning system, to send timely notifications and updated information of institutional events when the user is inside the university campus. NotiUFPS was developed using "Metodología Ágil para Dispositivos Móviles", a methodology developed by the "Grupo de Investigación en Desarrollo e Ingeniería de Software, Universidad Francisco de Paula Santander, San José de Cúcuta, Colombia", which consolidates development practices recognized as Scrum and XP.